Out for blood [large type] : a Matthew Redd thriller - Steck, Ryan (Thorndike Press large print Christian fiction series., 2024)
"Gavin Kline, executive assistant director of the FBI's Intelligence Directorate, is escorting a high-value prisoner with the intel to bring down a global conspiracy when their plane comes under attack. In the aftermath, much of Kline's team is dead, but he recovers a phone from a member of the hit team that reveals another attack is imminent. This time they're going after Matthew Redd. With a snowstorm bearing down on Montana and no help in sight, Redd fights for survival in the harshest conditions. But when they take the fight to his hometown, he'll need all his allies at his back to save what he holds most dear." --